Diagnóstico general y propuestas técnicas de mejoras respecto a la geometría horizontal, el drenaje transversal, el señalamiento vial y posibles ampliaciones para la ruta 10 (Paraíso-Naranjo) - Padilla-Rodríguez, Donald David (Instituto Tecnológico de Costa Rica, 2017)
This document contains the technical guidance required to perform a general diagnosis of the state of the horizontal geometry, the drainage system and of the road signing for the rute number 10 (Paraíso-Turrialba) with the objetive of providing the corresponding technical proposals related to the proper adjustments. The description of the geographic information system ArcGis use, and of AutoCAD Civil 3D use is presentend, as well as the use of smartphone applications in order to identify the state of the road infraestructura elements in study, namely: road’s transverse sewers, bus stops, gutlers, shoulders, general road demarcation, and bridges of the route. Besides, it contains an analysis of the road transverse sewers for a return period of 25 years and finally, using AutoCAD Civil 3D and satelital images of Google Earth, and the road geometrical design formulas, contains an analysis of the design speed normalization, and of capacity, with the objective of projecting more adecuate, and better levels of design, security and service for the route.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Infraestructura; Sistemas de información geográfica; Alcantarillas; AutoCAD; Seguridad